PENGARUH IKLAN DAN KEPERCAYAAN TERHADAP MINAT BELI KONSUMEN PADA MARKETPLACE BLIBLI.COM: (Survei pada Mahasiwa Fakultas Ekonomi dan Bisnis Universitas Kuningan) - Elsa Rinjani; Suhardi, Dadang; Komarudin, Munir Nur (Digital Business and Entrepreneurship Journal, 2023)
This research aims to determine the influence of advertising and trust on purchasing interest in the Blibli.com marketplace. The population in this study were all students from the Faculty of Economics and Business, Kuningan University, namely 2,177 people. Determination of sample size was based on the Slovin formula and a sample size of 96 respondents was obtained purposively. The research method that the author uses in this research is a survey method using a questionnaire distributed via Google Forms. The data collection technique that the author uses in this research is a questionnaire with measurements using an interval scale. The data obtained was then processed and analyzed using a multiple linear regression model with the help of the SPSS version 23 application. Hypothesis testing was carried out using verification analysis techniques based on the t-test and F-test. The results of the study showed that: (H1) advertising variables have a positive and significant effect on interest purchase, (H2) the trust variable has a positive and significant effect on purchase interest, and (H3) the advertising and trust variables simultaneously influence purchase interest.  Keywords: advertising; trust; buying interest